Dinardokanshones A and B, two unique sesquiterpene dimers from the roots and rhizomes of Nardostachys chinensis. Issue 43 (21st October 2015) - Wu, Hong-Hua; Chen, Ying-Peng; Ying, Shu-Song; Zhang, Peng; Xu, Yan-Tong; Gao, Xiu-Mei; Zhu, Yan
Graphical abstract: Abstract: Dinardokanshones A (1 ) and B (2 ), two unique sesquiterpene dimers were isolated from the roots and rhizomes of Nardostachys chinensis Batal. (Valerianaceae). Their structures were revealed by extensive spectroscopic analysis, and the absolute configurations were established by reported rules and computational electronic circular dichroism (ECD) method. Dinardokanshone B characteristically contains an aristolane lactone with an unusual 3/5/5/6 tetracyclic ring system. Based on a high-content assay for testing serotonin transporter (SERT) function, the two compounds showed significant enhancement effects on SERT activity.